2016
DOI: 10.1002/lt.24452
|View full text |Cite
|
Sign up to set email alerts
|

Role of patient factors, preferences, and distrust in health care and access to liver transplantation and organ donation

Abstract: Despite major improvements in access to liver transplantation (LT), disparities remain. Little is known about how distrust in medical care, patient preferences, and the origins shaping those preferences contribute to differences surrounding access. We performed a single-center, cross-sectional survey of adults with end-stage liver disease and compared responses between LT listed and nonlisted patients as well as by race. Questionnaires were administered to 109 patients (72 nonlisted; 37 listed) to assess demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…Perhaps it is because 80% of Micronesians in our study had hepatitis B, a screenable disease, that allowed earlier detection and the opportunity for curative therapies and better survival. Other U.S. studies have suggested that minorities are less likely to receive transplant due to differences in education, insurance, and patient perception of involvement in their care [20,21]. However, the Micronesians in our study had similar socioeconomic parameters and were able to overcome barriers to transplant.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Perhaps it is because 80% of Micronesians in our study had hepatitis B, a screenable disease, that allowed earlier detection and the opportunity for curative therapies and better survival. Other U.S. studies have suggested that minorities are less likely to receive transplant due to differences in education, insurance, and patient perception of involvement in their care [20,21]. However, the Micronesians in our study had similar socioeconomic parameters and were able to overcome barriers to transplant.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies on ethnic disparities in HCC cite culturally competent education and effective communication as key factors to improve care for minorities [20]. In Hawaii, we have several health clinics that readily refer patients to our liver center and are equipped with interpreters who speak various Micronesian dialects.…”
Section: Discussionmentioning
confidence: 99%
“…Wilder et al also show that patients were aware of this disparity. Specifically, fewer than 30% of blacks believed that minorities get equal access to liver transplant compared to over 50% of whites . Other studies also support the finding that blacks are aware of this disparity and are more likely to feel that race, income, and sex influence their care …”
mentioning
confidence: 89%
“…Wilder et al also found that blacks were less likely to consider becoming an organ donor than whites. This disparity did not appear to stem from religious or moral beliefs.…”
mentioning
confidence: 98%
“…Failure to refer patients to LT centres, or delaying their referral, and/or excessively selective screening practices at LT centres are possible reasons why potentially eligible LT candidates with ESLD have limited access to waiting lists. Although the estimates are only approximate ( because of methodological bias), there is published evidence of such omitted referrals and low rates of ESLD patients on waiting listing . Data on the prevalence of referrals to LT centres coming too late are scarce, and limited to patients with HCC .…”
Section: Interaction Between Hepatologists and Transplant Centres: Homentioning
confidence: 99%